Ratio Legis Tanggung Jawab Sosial dan Lingkungan Perusahaan dalam Menuju Harmoni Interaksi Perusahaan, Pemerintah dan Masyarakat - Deswina Maharani, Citra Ayu; Arifudin, Nur; Kurahman, Fauzi; Galih Ray Alfaries, Muhammad (UNES Law Review, 2024)
Corporate Social Responsibility (CSR) is a concept that states an organization (Company) has a responsibility towards consumers, employees, shareholders, communities and the environment in all aspects of the company's operations. For example, regarding problems that impact the environment, such as pollution, waste, product safety and labor. Based on Positive Law "Companies that carry out business activities in the field and/or related to natural resources are obliged to carry out Corporate Social Responsibility". This is because the company must have benefits that can be felt by the business environment and society. However, in reality, not all companies are able to realize Social and Environmental Responsibility is implemented it is not carried out well. The article with the title "Legis Ratio of Corporate Social and Environmental Responsibility towards Harmonious Interaction between Companies, Government and Society" was created for answering questions regarding how to implement Corporate Social Responsibility in companies in Indonesia, Why the Implementation of Corporate Social Responsibility in Companies in Indonesia is Still Many Obstacles and How to Create Harmony in the Interaction of Companies, Government and Society. Hoped that the results of this writing can be applied to create harmony in the interactions between companies, government and society.